The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1128/jvi.03627-14
|View full text |Cite
|
Sign up to set email alerts
|

Early Kinetics of the HLA Class I-Associated Peptidome of MVA.HIVconsv-Infected Cells

Abstract: Cytotoxic T cells substantially contribute to the control of intracellular pathogens such as human immunodeficiency virus type 1 (HIV-1). Here, we evaluated the immunopeptidome of Jurkat cells infected with the vaccine candidate MVA.HIVconsv, which delivers HIV-1 conserved antigenic regions by using modified vaccinia virus Ankara (MVA). We employed liquid chromatography-tandem mass spectrometry (LC-MS/MS) to identify 6,358 unique peptides associated with the class I human leukocyte antigen (HLA), of which 98 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…This MHC-peptidome study and others in viral infections (9,15,16) or in B cell lines (30,(42)(43)(44)(45) identified clusters of nested peptides. They include optimal epitopes as well as N-and/or Cextended peptides potentially presentable by several HLAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This MHC-peptidome study and others in viral infections (9,15,16) or in B cell lines (30,(42)(43)(44)(45) identified clusters of nested peptides. They include optimal epitopes as well as N-and/or Cextended peptides potentially presentable by several HLAs.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of vaccinia virus-derived peptides over 12 h (15) and the presentation of both modified vaccinia Ankara (MVA) peptides and HIV peptides from Jurkat cells infected with MVA expressing HIV protein fragments followed during 6 h (16) showed variations in epitope presentation over time. While peptide presentation was linked to protein expression (15,16), defective translation products (defective ribosomal products [DRiPs]) may also contribute to various extents to the pool of MHC-I peptides displayed by cells (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, Ternette et al recently found that 5% of dimethyl sulfoxide in liquid chromatography solvents enhanced the electrospray ionization of HLA class I peptides, improving the total ion count by approximately twofold (personal communication) (72,73). However, the effect of enhancing electrospray ionization and sensitivity might depend on the type of emitter source as well as specific parameters such as voltage, temperature, and gas flow.…”
mentioning
confidence: 99%
“…Three accepted methods for the isolation of MHC class I or class II peptides have emerged in the last decades: 1) mild acid elution, where the cell surface MHC class I but not class II complexes are denatured at approximately pH 3.3, therefore releasing the MHC class I peptides while leaving the cells intact18; 2) immunoaffinity purification of the endogenous pMHC from cells, tissues, and body fluids using MHC‐specific monoclonal antibodies bound to solid support19; and 3) immunoaffinity purification of transfected recombinant soluble or membrane‐anchored MHC molecules using anti‐MHC antibodies or antibodies against affinity tags 20. Stable isotope labeling of the cellular proteins has been used in order to follow their synthesis, degradation dynamics, and the MHC presentation of their derived peptides and to assess the degree to which pMHC is derived from defective ribosome products21 and has been applied for the identification of pathogen‐derived pMHC 22. A comprehensive description of such advanced experimental approaches is required, and in this section, we cover aspects related to the extraction of pMHC from the biological samples and their preparation and storage prior to the LC‐MS/MS characterization.…”
Section: Preparation Of Pmhc Samplesmentioning
confidence: 99%